Effects of Overweight/Obesity on Motor Performance in Children: A Systematic Review - Barros, Waleska Maria Almeida; Silva, Karollainy Gomes da; Silva, Roberta Karlize Pereira; Souza, Ana Patrícia da Silva; Silva, Ana Beatriz Januário da; Silva, Mariluce Rodrigues Marques; Fernandes, Matheus Santos de Sousa; Souza, Sandra Lopes de; Souza, Viviane de Oliveira Nogueira (Frontiers in Endocrinology, 2022)
Childhood obesity is a serious public health problem. Childhood obesity and overweight are associated with the appearance of coordination deficit disorder and can cause impaired motor performance. We searched online databases for all related articles using comprehensive international databases from the Medline PubMed Institute, Web of Science, ScienceDirect, SCOPUS and PsycINFO up to December 20, 2020. Overall, 33 studies were included in this systematic review. The present review demonstrated that children with higher percentage of body fat had lower levels of moderate to vigorous physical activity, as well as decreased levels of gross motor coordination, as shown by tests for neuromuscular performance. These results corroborate the hypothesis that overweight and obesity in children and adolescents are associated, not only with insufficient performance during gross motor coordination activities, but also with a greater risk to physical health.